Longitudinally extensive transverse myelitis after epidural anaesthesia in childbirth - Damnjanović, Dijana; Zamurović, Milena; Vranjanac, Aleksandar (Vojnosanitetski pregled, 2023)
Introduction. Neurological complications related to epidural anesthesia are rare, but it is necessary to recognize and diagnose them as early as possible, in order to start appropriate therapy and prevent further neurological damage. One of the rare complications of regional anesthesia described in this paper is longitudinal extensive transversal myelitis (LETM). Case report. A 32-year-old patient, who gave birth by Caesarean section in due term, developed LETM the very same day. Considering the neuroradiological findings that indicated to the long central lesion in the thoracic and lumbar spine, and an expected reaction to the applied immunotherapy (immunosuppressive therapy and therapeutic plasma exchange), a diagnosis of LETM was made. Even with all the therapy and regression of the lesions, the patient could not stand up without support. During the subsequent treatment, according to the instructions of the physiatrist, physical therapy was carried out, to which the patient responded slowly but favorably, with a gradual return of the function of the lower extremities. Conclusion. Early diagnosis and timely treatment of LETM are crucial for the prognosis of the disease and the early recovery of the patient.
Keywords: anesthesia, epidural; diagnosis; drug-related side effects and adverse reactions; delivery, obstetric; myelitis, transverse; paralysis